Assessment of innovative potential of farmers and homestead land owners - Khamraeva Sayyora; Ochilova Nargiza (E3S Web of Conferences, 2024)
In the conditions of globalization, ensuring the food security of the population in the world community, based on the sustainable development of agriculture, requires the sector to be flexible to the external changing environment, to be effective in various innovations and scientific and technical development. Therefore, in the world's prestigious scientific research institutions, scientific research is being carried out in such directions as the introduction of innovative methods of agricultural production, the organization of non-traditional production and the production of environmentally friendly agricultural products to ensure the food security of the population. In particular, special attention is paid to scientific research aimed at solving problems such as the organization of vertical agricultural production on small land areas, the creation of disease-resistant and competitive varieties and hybrids in farming, and the introduction of resource-saving high-efficiency innovative technologies. In this article, the innovative activities of farms and homesteads operating in Kashkadarya region were studied and the innovative potential index of farms and homestead landowners in the regions was determined based on 5 indicators.